John Berger's Fictional Acts of Faith - Watson, Margaret Diane (My University, 1990)
John Berger is well known to a certain segment of the general public, especially in England and Europe, for his critical art essays and reviews, and is thought of as a populist of aesthetics.
This thesis constitutes the first comprehensive examination of Berger's fiction. It treats Berger as a thinker and a writer-- not simply as a populist of aesthetics-- and therefore broadens the context in which he is usually considered. Chapter One provides an overview of Berger's methodology and aesthetlc. Chapter Two examines his first three novels in terms of his empathetic response to the class of people with which these novels are concerned, the nature of the dream as manifest in these novels, and Berger's concept of the heroic. Chapter Three is a close reading of G. and the theories of time it sets forth. Chapter Four considers the views of memory and experience in Berger's last two works of fiction, and the reasons for his turning to traditional narrative form. The work as a whole traces Berger's struggle to get "close to the face of experience".
By examining each of Berger's works of fiction to determine both how each is informed by his critical perspective and ideology and how each manifests a stage in his evolution as a writer and thinker, this thesis makes the claim that Berger deserves as much recognition for his creative writing as he has received for his (distinctly creative) criticism. This work maintains that though his fiction moves increasingly in the direction of philosophical speculation, it loses none of its political impact.
Keywords: English Language and Literature; English Language and Literature